The Impact of Using Management Information Systems on Customer Satisfaction Levels - Maulana Irsyad, Raihan; Nasution , Muhammad Irwan Padli (Digital Innovation, 2025)
This study aims to analyze the impact of management information system usage on customer satisfaction levels in a company. Management information systems have become one of the essential elements in enhancing operational efficiency and the quality of services provided by companies to their customers. In this study, data was collected through surveys of customers who interact with the management information system in the company. The analytical method used is regression analysis to evaluate the relationship between the variables of management information system usage and customer satisfaction levels. The results of the study show that the use of management information systems has a positive and significant impact on increasing customer satisfaction levels. Customers feel more satisfied due to faster access to information, more responsive services, and improved service quality. These findings emphasize the importance of effective management information system implementation to support customer satisfaction strategies and foster customer loyalty. Therefore, companies are advised to continuously develop and update their management information systems to enhance customer satisfaction and retention.